Pengaruh Metode Silaba Terhadap Keterampilan Membaca Permulaan dalam Pembelajaran Bahasa Indonesia di Kelas II SDN 1 Karangasem - Mauliani Azzahra; Erna Labudasari; Anih Sumiati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research was motivated by the method used by teachers in reading skills which was less effective and the lack of reading skills in students in class 2 of SDN 1 Karangasem. The aim of the research is to determine the reading skills of grade 2 students at SDN Karangasem, to determine the application of the silaba method in grade 2 students at SDN Karangasem and to determine the effect of the silaba method on reading skills for elementary school students in learning Indonesian at SDN 1 Karangasem. The method used in this research is quantitative pre-experiment with a one group pretest posttest design. The subjects in this research were 18 (eighteen) students. Data collection techniques, pretest, posttest, observation, student activity sheets and documentation. Data analysis techniques include data collection, normality test, N-gain and hypothesis. From the results of the research that has been carried out, it can be concluded that (1) The reading skills of grade 2 students at SDN 1 Karangasem have improved after being treated using silaba. With an average initial pretest result of 69.17 before being given treatment and an average posttest result after being given treatment being 93.33. (2) The application of the silaba method in grade 2 students at SDN 1 Karangasem is very effective, this is proven by the results of pretest and posttest research from the initial category being quite fluent before being given treatment to being fluent after being given treatment. (3) The results of the pretest and posttest in the experimental class were better because they used the silaba method to help students with their reading skills. The results of the T Paired Sample Test calculation show a significant 0.001 because it is significant <0.05, so it can be concluded that Ho is rejected and Ha (Alternative Hypothesis) is accepted. It can be interpreted that on average before and after using the silaba method there is a change in reading skills. Conclusion: There is an influence on reading skills using the silaba method in learning Indonesian in class 2 of SDN I Karangasem.